2021
DOI: 10.3390/cancers13205093
|View full text |Cite
|
Sign up to set email alerts
|

[99mTc]Tc-DB15 in GRPR-Targeted Tumor Imaging with SPECT: From Preclinical Evaluation to the First Clinical Outcomes

Abstract: Diagnostic imaging and radionuclide therapy of prostate (PC) and breast cancer (BC) using radiolabeled gastrin-releasing peptide receptor (GRPR)-antagonists represents a promising approach. We herein propose the GRPR-antagonist based radiotracer [99mTc]Tc-DB15 ([99mTc]Tc-N4-AMA-DGA-DPhe6,Sar11,LeuNHEt13]BBN(6-13); N4: 6-carboxy-1,4,8,11-tetraazaundecane, AMA: aminomethyl-aniline, DGA: diglycolic acid) as a new diagnostic tool for GRPR-positive tumors applying SPECT/CT. The uptake of [99mTc]Tc-DB15 was tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…This is essential because the injected peptide mass in this study was two orders of magnitude higher than the injected mass of agonistic bombesin derivative, which was reported to induce adverse side effects [ 23 ]. On the other hand, the absence of the agonistic action-related side effects is in good agreement with the data concerning an evaluation of other imaging probes based on GRPR antagonists, which were injected within the same mass range, i.e., 10–56 µg/injection [ 20 , 24 , 25 ]. The absence of any pharmacological effect from GRPR antagonists should improve the perception of the imaging procedure by patients and help to avoid side-effect-related artifacts.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is essential because the injected peptide mass in this study was two orders of magnitude higher than the injected mass of agonistic bombesin derivative, which was reported to induce adverse side effects [ 23 ]. On the other hand, the absence of the agonistic action-related side effects is in good agreement with the data concerning an evaluation of other imaging probes based on GRPR antagonists, which were injected within the same mass range, i.e., 10–56 µg/injection [ 20 , 24 , 25 ]. The absence of any pharmacological effect from GRPR antagonists should improve the perception of the imaging procedure by patients and help to avoid side-effect-related artifacts.…”
Section: Discussionsupporting
confidence: 88%
“…The hepatobiliary excretion of [ 99m Tc]Tc-maSSS-PEG 2 -RM26 was the highest among other GRPR antagonists tested in clinics and was similar to the excretion of [ 99m Tc]Tc-RP527, a GRPR agonist [ 26 ]. Predominantly renal excretion was observed for [ 68 Ga]Ga-BAY-7548 [ 27 ], [ 64 Cu]Cu-CB-TEA2-AR06 [ 25 ], [ 68 Ga]Ga-SB3 [ 28 ], [ 68 Ga]Ga/[ 177 Lu]Lu-RM2 [ 24 , 29 ], [ 68 Ga]Ga-NeoBOMB1 [ 30 ], and [ 99m Tc]Tc-DB15 [ 20 ]. Up to 60-70% of injected activity for these short peptides is excreted to urine within 4 h [ 31 ] and the reported images for these compounds reveal appreciable activity uptake in the urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a following side-by-side comparison of [ 99m Tc]Tc-DB1 with the agonist-based [ 99m Tc]Tc-DB4, [ 99m Tc]Tc-DB1, despite the lack of internalization, achieved higher tumor uptake and faster washout from GRPR-positive tissues [ 56 ]. It should be noted that efforts to prolong tumor retention involved the introduction of different linkers and amino acid replacements, eventually revealing the Sar 11 -analog [ 99m Tc]Tc-DB15 as a promising candidate for clinical translation [ 28 , 57 ]. The first results in patients with advanced breast cancer revealed an excellent pharmacokinetic profile of [ 99m Tc]Tc-DB15, whereby, the tracer visualized several bone and soft tissue metastases on SPECT/CT, while being well tolerated [ 28 ].…”
Section: From Agonists To Antagonists In Grpr-targeting Radioligand Developmentmentioning
confidence: 99%
“…The recent implementation of antagonistic bombesin analogues has mitigated the adverse effects, which were previously observed after injection with agonistic analogues. Nock and co-workers [ 10 ] have demonstrated that incorporation of the unnatural amino acid sarcosine instead of Gly 11 in the GRPR antagonist demobesin appreciably improved in vivo stability of this peptide. The tracer, [ 99m Tc]Tc-DB15, demonstrated excellent targeting of GRPR-expressing human breast and prostate cancer xenografts in mice.…”
mentioning
confidence: 99%